Beyond barriers: exploring foreign language learning experiences of students with diverse learning needs in four European countries - Marianthi Karatsiori; Trisevgeni Liontou; Ewa Domagała-Zyśk; Karin Vogt; Milena Košak Babuder; Mojca Poredoš (Frontiers in Education)
While foreign language learning is increasingly recognized as crucial for educational and social inclusion, the experiences of students with diverse learning needs in foreign language classrooms remain understudied. This study investigated the relationship between Personal Engagement (PE) and Learning Attitudes (LA) among students with diverse learning needs in foreign language learning contexts across four European countries (Greece, Germany, Slovenia, and Poland). The study involved 95 students (aged 8-25) with various learning needs: visual impairment (n = 16), deafness/hard of hearing (n = 14), physical/motor impairment (n = 32), and learning difficulties (n = 33). Data were collected through interviews and standardized questionnaires examining both PE and LA, with findings analyzed using both qualitative and quantitative methods. Results revealed that LA scores consistently exceeded PE scores across all groups, with students with physical impairments showing the strongest correlation between engagement and attitudes (r = 0.674, p < 0.001), while students with visual impairments demonstrated high LA despite moderate engagement levels. Students with diverse learning needs maintain remarkably positive attitudes toward foreign language learning despite varying engagement levels, suggesting that educational barriers may be more related to access and delivery methods than to students’ willingness to learn. This emphasizes the need for tailored support strategies that can transform positive attitudes into fuller engagement across different types of learning needs.